2002
DOI: 10.1042/bj20020822
|View full text |Cite
|
Sign up to set email alerts
|

The metalloendopeptidase nardilysin (NRDc) is potently inhibited by heparin-binding epidermal growth factor-like growth factor (HB-EGF)

Abstract: Nardilysin (N-arginine dibasic convertase, or NRDc) is a cytosolic and cell-surface metalloendopeptidase that, in vitro, cleaves substrates upstream of Arg or Lys in basic pairs. NRDc differs from most of the other members of the M16 family of metalloendopeptidases by a 90 amino acid acidic domain (DAC) inserted close to its active site. At the cell surface, NRDc binds heparin-binding epidermal growth factor-like growth factor (HB-EGF) and enhances HB-EGF-induced cell migration. An active-site mutant of NRDc f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…However, the precise mechanism by which the formation of the complex is enhanced has not been clarified. NRDc is a cytosolic enzyme with no signal peptide; however, it is exported out of the cell by unknown mechanisms (27)(28)(29). The translocation of NRDc from the cytosol to the cell surface might nicely explain how the formation of a complex with TACE is enhanced by PMA without any significant change in the total expression level of the protein.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the precise mechanism by which the formation of the complex is enhanced has not been clarified. NRDc is a cytosolic enzyme with no signal peptide; however, it is exported out of the cell by unknown mechanisms (27)(28)(29). The translocation of NRDc from the cytosol to the cell surface might nicely explain how the formation of a complex with TACE is enhanced by PMA without any significant change in the total expression level of the protein.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the enzyme is widespread and especially high in testis, heart, and skeletal muscle (26). NRDc is expressed mainly in the cytoplasm, but interestingly, it is also exported out of cells and distributed on the cell surface, although it has no apparent signal peptide sequence (27)(28)(29). While examining the biological significance of the binding of NRDc to pro-HB-EGF, we found that NRDc enhances ectodomain shedding of the growth factor.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Deletion of the sequence corresponding to exon 4 in a pIRES2-enhanced green fluorescent protein (EGFP) recombinant vector containing a mouse PC5A cDNA (pIR-mPC5A-V5) was achieved by a two-step PCR (15). Two sense and antisense primers reconstituting the exon 3-to-exon 5 junction (5Ј-GTATGTGGTACATGGATGCTCTGGCAAGTTGCG and 5Ј-GCA ACTTGCCAGAGCATCCATGTACCACATACTTGGCC) and two distal primers, located upstream of a unique EcoRI site in the polylinker (sense, 5Ј-CGGACT CAGATCTCGAGC) and downstream of a unique BsmBI in the mPC5A sequence (antisense, 5Ј-CACATCGCAACTTGCCATGTACCACATACTTGGCC), led to the final amplification of a 1,180-bp fragment that was subcloned in a pDRIVE vector (QIAGEN, Mississauga, Ontario, Canada).…”
Section: Methodsmentioning
confidence: 99%